The Economic Losses of University Hospitals due to the No Payment System for Forensic Reports - Altun, Gürcan (The Bulletin of Legal Medicine, 2004)
The aim of this paper which reference to Trakya University Hospital draws attention to economic losses of university hospitals due to lack of a system for payment of forensic reports. In this paper, forensic documents of Trakya University Hospital, covering the period January 2003- December 2004, were reviewed. We established the institutions that ask to prepare forensic reports and queries during this period. These institutions were offices of the public prosecutor and court, police, gendarme, and the other institutions (such as management of jails, notary public offices). In 2003 and 2004 Trakya University Hospital forensic reports were 471 and 653, respectively. We established annual rate of increase to the number of prepared forensic reports (39%) and unit prices (50-60%) between 2003 and 2004. Economic losses of no payment for preparing forensic reports in 2003 and 2004 years have been calculated as 9.647.500.000 TL and 19.420.000.000 TL, respectively. A total economic loss for two years was 29.067.500.000 TL. As a conclusion, the prices of contributing forensic expertise services by university for medicolegal cases must be measured according to price list of Council of Forensic Medicine. Managements of the universities with the help of Council of Higher Education should apply to Ministry of Finance for solving this problem.Key words: Forensic report, cost, university hospital
Keywords: forensic report; cost; university hospital